The End of Techno-Critique: The Naked Truth about 1:1 Laptop Initiatives and Educational Change - Weston, Mark E.; Bain, Alan (The Journal of Technology, Learning and Assessment, 2010)
This article responds to a generation of techno-criticism in education. It contains a review of the key themes of that criticism. The context of previous efforts to reform education reframes that criticism. Within that context, the question is raised about what schools need to look and be like in order to take advantage of laptop computers and other technology. In doing so, the article presents a vision for self-organizing schools.